Students’ Interest in Learning English through YouTube (A Case Study in Senior High School of Sekolah Alam Cikeas Bogor) - Shopia, Khilda; Sabila, Dara; Purnawati (STAIRS: English Language Education Journal, 2022)
Technology advancement, including YouTube, enables various media easily integrated into the teaching and learning process and supports the students’ digital media literacy. However, in the implementation, some teachers find difficulties in engaging the students’ interest in using YouTube to support the teaching and learning process. This study was conducted to investigate why YouTube is considered the prominent media in Sekolah Alam Cikeas to engage students’ interest in English learning. A case study was used to analyze the phenomenon while questionnaires and interviews were used in collecting the data. Likert scale was used to analyze the data by using 5 aspects. The result illustrated Strongly Agree as the dominant answer from students. YouTube can help them in learning English and it plays a useful and meaningful role in the learning process. Most of the students agree that the usage of YouTube in the classroom is appropriate and can engage students’ interest in learning English in the classroom. Besides, YouTube also can help students to train in digital media literacy. Thus, YouTube is one of the media that supports students’ interest to engage in the learning process.